Pure proton therapy for skull base chordomas and chondrosarcomas: A systematic review of clinical experience - Nie, Menglin; Chen, Liying; Zhang, Jing; Qiu, Xiaoguang (Frontiers in Oncology, 2022)
Background Skull base chordoma and chondrosarcoma are exceptionally rare bone tumors with high propensity for local recurrence. Different postoperative radiation modalities are often used to improve the clinical efficacy. Proton therapy (PT) might be among the most promising ones because of the unique ballistic characteristics of high-energy particles. However, previous meta-analysis often included studies with combined radiation techniques. No systematic review to date has directly analyzed the survival and toxicity of pure PT for these two types of malignancies. Methods By following the PRISMA guidelines, a systematic search of three databases was conducted. Articles were screened and data were extracted according to a prespecified scheme. R 4.2.0 software was used to conduct the meta-analysis. Normal distribution test was used for the incidence rate of each subgroup. Results A total of seven studies involving 478 patients were included in this analysis. The quality of included articles ranged from moderate to high quality. All patients were histopathologically diagnosed with chordoma or chondrosarcoma, and the follow-up time of the cohort ranged from 21 to 61.7 months. For PT planning, the median target volume ranged from 15 cc to 40 cc, and the administered median dose varied from 63 to 78.4 GyRBE at 1.8–2.0 GyRBE per fraction. The 1-, 2-, 3-, 5-, and 7-year local control and overall survival rates were 100%, 93%, 87%, 78%, and 68%, and 100%, 99%, 89%, 85%, and 68%, respectively. The late grade 3 or higher toxicities were reported in only two involved articles. Conclusions Until now, medical centers worldwide have exerted PT to improve outcomes of skull base chordomas and chondrosarcomas. PT not combined with other radiation modalities showed favorable local control and survival with a low incidence of severe radiation-induced toxicities, which manifests promising clinical benefits. However, high-quality evidence is still limited, requiring future clinical trials and prospective studies in selected patients.